Minimum Inhibitory Concentration of Marine Microalgae Dunaliella salina on Fish Pathogenic Bacteria Edwardsiella tarda - Rusmawanto, Rusmawanto; Prajitno, Arief; Yuniarti, Ating (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Dunaliella salina is a type of marine microalgae. The objective of this research were investigated the effect of D. salina to inhibit the growth of E. tarda. The method used in this study was examined antibacterial activity of D. salina using disc diffusion and co culture test. The secondary metabolite compound in D. salina was tested using phytochemical screening and FTIR methods. The results obtained D. salina extracted using n-hexane showed the best activity for inhibiting the growth of E. tarda. Minimum concentration of 100 mg.L-1 crude extract can inhibit E. tarda with a total of bacterial colonies 137x1011 CFU.mL-1. The phytochemical test results showed that D. salina extract using n-hexane contained flavonoids, saponins, alkaloids, terpenoids and phenols. The FTIR analysis showed phenol and carotene compounds are one of the secondary metabolites that can be used as antibacterial. It can be concluded that the extract has strong antibacterial activity against E. tarda and potentially as antibacterial in aquaculture.